PENGARUH INSENTIF DAN JAMINAN SOSIAL TERHADAP SEMANGAT KERJA KARYAWAN (Studi Kasus Pada Karyawan SDM PT. Perkebunan Nusantara V Pekanbaru) - Suyetno, Aan Rudi; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the effect of incentives and social security on employee morale (Case Study on HR Employees of PT Perkebunan Nusantara V Pekanbaru). Morale is the desire and seriousness of a person to do their job well and to be disciplined to achieve maximum productivity so that company goals can be achieved. To increase employee morale, it is necessary to first investigate what factors affect employee morale. Where the independent variables in this study are incentives and social security, and the dependent variable is morale.Â The population in this study were employees of PT.Perkebunan Nusantara V Pekanbaru with a sample of 105 people who were calculated using the method of Issac and Michael. Types and sources of data in the study were primary data and secondary data using questionnaires, interviews and company documents. The data analysis used is to use the help of the SPSS ver 26 application for windows.Â The results showed that partially incentives and social security had a significant effect on employee morale and simultaneously incentives and social security had a significant effect on employee morale of PT Perkebunan Nusantara V Pekanbaru's human resources.Keywords: Incentives, social security, moral